If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2y + -3(2y + 6) = 114 Reorder the terms: y + 2y + -3(6 + 2y) = 114 y + 2y + (6 * -3 + 2y * -3) = 114 y + 2y + (-18 + -6y) = 114 Reorder the terms: -18 + y + 2y + -6y = 114 Combine like terms: y + 2y = 3y -18 + 3y + -6y = 114 Combine like terms: 3y + -6y = -3y -18 + -3y = 114 Solving -18 + -3y = 114 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -3y = 114 + 18 Combine like terms: -18 + 18 = 0 0 + -3y = 114 + 18 -3y = 114 + 18 Combine like terms: 114 + 18 = 132 -3y = 132 Divide each side by '-3'. y = -44 Simplifying y = -44
| 8x-7y= | | .8333333333+.2t=.6666666667 | | -abs(x+3)-4=-14 | | 8x+5=36x | | -(z+9)+(4z+1)=-3(z+1) | | h=-16t^2+12t+40 | | 8b+-7=7b-2 | | c=50l^2+30000 | | 6(x-6)-8(x-2)=-16 | | 3x+18=10x-15 | | (x+2)+(x+4)=20+x | | 3K-6=-9 | | 5w-12=63 | | 6(2z-1)-2(7+3)=5(z+1) | | 9(v+2)-3v=3(2v+1)-8 | | 7(4-t)+3=-3(t-3)-6 | | y=7.5X+10 | | 10(a+1)-14a=9-(4a+1) | | 8(x-9)-4=-76 | | -8(2t^2+8t-6)=0 | | 5/7x-7=53 | | A+(-35)=-75 | | 25x-4=40x+2 | | -6.75+2.25x=x | | 9(x-2)+8=4x+5(-2+x) | | 6[3-(-8x-2)]=240x+78 | | 3(x-2)=5(x-3)+2 | | A+(-35)=75 | | 6(3n-1)+9=3(6n+3) | | 2x+4-7(x+1)=3x+4 | | 4y^2+x=0 | | -23/24=11/12+5x/6 |